If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15X + -1 = Y Reorder the terms: -1 + 15X = Y Solving -1 + 15X = Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 15X = 1 + Y Combine like terms: -1 + 1 = 0 0 + 15X = 1 + Y 15X = 1 + Y Divide each side by '15'. X = 0.06666666667 + 0.06666666667Y Simplifying X = 0.06666666667 + 0.06666666667Y
| 5x+14=3x+8 | | 20-x+(2*5)=20 | | -7y-10x+11=0 | | 20-x+(2*5)=7 | | 6tan(x)+5=3 | | 15-4x=10x+64 | | -9+8x=-10y | | −4/9x-8/9=1/2x-1/2 | | 3+r=-4 | | -2Y=5X-1 | | f(x)=155 | | 3x-12=55 | | Cos(60)16=x | | 3X*10=12 | | 3//=4/12 | | N/72=5/8 | | 6/7=11/x | | N/100=5/25 | | 6/11=7/x | | 12x^2+34x-6=0 | | 116=56+2w | | 6+(y+4)=2y-(5y-18) | | -4.2=-0.84(a+4) | | -13w^2+38w-15=0 | | 5x+12=2+3 | | 10/17=h/204 | | X+78=x+41+95 | | 2(3x+7)=11x+5-5x+9 | | Y=Zx+1 | | 0=250t+9000 | | 3X*12=15 | | 4x=y+19 |